Interrelation of strategic planning with human resources planning through performance appraisal systems theory and field research on Turkish banks - Cemali, Haslet (My University, 1991)
unknown
Keywords: Genel yönetim; İŞLETMELER-PERFORMANS ÖLÇÜMÜ; Personel yönetimi; PERSONEL YÖNETİMİ-PLANLAMA